Immigration and the nation-state the United States, Germany, and Great Britain - Joppke, Christian (Oxford : Oxford University Press, 1999)
Comparing the postwar politics of immigration control and integration in the US, Germany, and Great Britain, set against diagnoses of nation-states diminished by globalization and international human rights regimes and discourses, the author argues that nation-states have proved remarkably resilient, at least in the face of immigration.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Citizenship -- United States; Citizenship -- Germany; Citizenship -- Great Britain; United States -- Emigration and immigration -- Government policy; Germany -- Emigration and immigration -- Government policy; Great Britain -- Emigration and immigration -- Government policy